Artistas Ou Alienados: Repercussões Críticas Das Primeiras Exposições Com Obras De Internos Do Centro Psiquiátrico Nacional - Araujo, Paula Vaz Guimaraes De [UNIFESP] (2017)
The master's research presented here analyzes the critical repercussions of the exhibitions "Painting of the alienated from the National Psychiatric Center" and "The Nine Artists from the Engenho de Dentro of Rio de Janeiro", the first exhibitions to present artistic works made by the inmates of the National Psychiatric Center. Eighty-four journalistic publications collected during this research - among brief essays, essays signed by public figures of the moment and art criticisms - will be used on this analysis. In addition to the art criticisms, the journalistic notes that have been considered here evidenciate the organization process of the exhibition, or, as is more frequent, are effective indexes of reception of certain modern art concepts, directed to a lay public. The intention behind this dissertation is not only to establish points of approximation and distance between the opinions of the different critics and journalists who spoke about the studied exhibitions, but to seek for the understanding of significant questions within the artistic and historical fields through these different points of view. Researches that have dealt with this problem, as well as the questions that have arised from the methodological challenges involved in this research about the relationship between Brazilian criticism and the visual productions of psychiatric patients, are also addressed throughout this dissertation.